The Eﬀect of Management Ownership, Institutional Ownership, Corporate Social Responsibility and Proftability to the Company’s Value - Darmawan, Akhmad; Nisa, Ainun; Rejeki, Sri (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2018)
This study is aimed to identfy the eﬀect of management ownership, insttutonal ownership, Corporate Social Responsibility (CSR), profitability to the company’s value. In this study, the company’s value is using proxy of Price Book Value (PBV). The samples were taken from 18 Goods Consumer Industry companies which are registered in the BEI on 2013-2016t. Whilst the data of the research was 72 samples and after cash-wised into 67 samples. The analysis method used for this study is multiple regression analysis. Based on this study’s result, it is resulted that the management ownership, institutional ownership, CSR, profitability is simultaneously having positive effect on the company’s value. CSR has positve eﬀect on the company’s value positvely, proftability has positve eﬀect on the company’s value signifcantly.